1987
DOI: 10.1111/j.1469-8137.1987.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

ZINC TOLERANCE IN BETULA SPP.

Abstract: SUMMARYClones of zinc-tolerant and non-tolerant genotypes of Betula pendula Roth, and B. pubeseens Ehrh. were cultured aseptically on media containing different concentrations of zinc. The location, concentration and form of zinc in root tissues of both groups of genotype were compared using various microanalytical techniques. At concentrations of zinc at which all genotypes were viable, there were no obvious differences between the tolerant and non-tolerant genotypes. When the roots were subjected to concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Sela et al (1988) reported localization of Cu (also Cd and U) in the aquatic fern Azolla filiculoides and van Steveninck et al (1990a,b, van Steveninck, van Stevenick & Fernando 1992) have investigated Zn (and Cd) localization in the aquatic angiosperm Lemna minor . Other reports have investigated grasses (Mullins et al 1985; van Steveninck et al 1987) and dicotyledonous plants (Mullins et al 1985; van Steveninck et al 1993, 1994), including a hyper‐accumulating herb (Vázquez et al 1992) and tree seedlings (Denny & Wilkins 1987; Jentschke, Fritz & Godbold 1991; Arduini, Godbold & Onnis 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sela et al (1988) reported localization of Cu (also Cd and U) in the aquatic fern Azolla filiculoides and van Steveninck et al (1990a,b, van Steveninck, van Stevenick & Fernando 1992) have investigated Zn (and Cd) localization in the aquatic angiosperm Lemna minor . Other reports have investigated grasses (Mullins et al 1985; van Steveninck et al 1987) and dicotyledonous plants (Mullins et al 1985; van Steveninck et al 1993, 1994), including a hyper‐accumulating herb (Vázquez et al 1992) and tree seedlings (Denny & Wilkins 1987; Jentschke, Fritz & Godbold 1991; Arduini, Godbold & Onnis 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed centripetal increase in Zn with the highest levels in the stele. Previous studies have emphasized Zn localization in parenchyma adjacent to vascular tissue in L. minor (van Steveninck et al 1990a), in cortical parenchyma in Deschampsia caespitosa (van Steveninck et al 1987), and the endodermis (Denny & Wilkins 1987; van Steveninck et al 1993, 1994). Mullins et al (1985) found that Zn accumulation bodies decreased centripetally in D. caespitosa and Anthoxanthum odoratum .…”
Section: Discussionmentioning
confidence: 99%
“…A Zn-sensitive clone had no such ability. Zinc-tolerant genotypes of Betula resisted zinc toxicity by controlling uptake of the metal into their tissues at higher external concentrations (Denny and Wilkins 1987). Zinc-tolerant genotypes of Betula resisted zinc toxicity by controlling uptake of the metal into their tissues at higher external concentrations (Denny and Wilkins 1987).…”
Section: B Toxicitymentioning
confidence: 99%
“…Macrophytes have been used during the last two decades for metal removal (Denny and Wilkins 1987). One such macrophyte Ipomoea aquatica is a semi-aquatic tropical plant grown as a leaf vegetable.…”
Section: Introductionmentioning
confidence: 99%